Convents of England IX - Mid XI Centuries - I. I. Boldyreva (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The historical features of Anglo-Saxon convents from the 9th to the middle of the 11th centuries are considered in the article. The scientific novelty of the study is due to the fact that in domestic historiography this issue has not been previously studied. The study is based on a wide range of historical evidence: hagiographic writings, biographies, letters, chronicles. The factors determining the decline of double monasteries in England in the 9th century are revealed. The data of Anglo-Saxon letters illustrating the conflicts of bishops and abbesses are analyzed. It is shown that in the late Anglo-Saxon period, despite the weakening influence of the abbesses, female monastic communities continued to maintain close ties with the royal house. The material well-being of women’s monasteries was often determined by the presence of representatives of the royal family among their inhabitants. Particular attention is paid to the history of Anglo-Saxon convents during the Benedictine reform initiated by King Edgar (959-975). The features of the relationship of queens with convents at the end of the 10th - middle of the 11th centuries are analyzed. The historical specificity of the involvement of conventions in the reform process was studied mainly on the basis of the history of the Wilton monastery, in which one of the most famous Anglo-Saxon ascetics - Saint Edith lived.